2007
DOI: 10.2134/agronj2005.0268
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Variability in Corn as Influenced by Growth Stage Using Optical Sensor Measurements

Abstract: Improving crop management inputs with remote sensing devices is an emerging technology. This study documented the progression of the normalized difference vegetative index (NDVI) during the life cycle of corn (Zea mays L.), evaluated the spatial variability of corn growth in terms of the CV (calculated from NDVI readings), and documented the relationships between NDVI, CV (calculated from NDVI), and grain and biomass yields and plant density. Four rows, 30 m in length, from two locations during 2 yr were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
44
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 14 publications
11
44
1
7
Order By: Relevance
“…Compared to Cluster B both cluster A and C have relatively larger absolute values (0.2-0.4) in NDVI residuals, indicating larger growth The correlation analysis summarized in Table 5 indicates that the NDVI residual derived from Landsat images reflects crop stress in the pre-silking period that in turn impacts final yield. This result is consistent with other studies that have found that NDVI from the middle to late vegetative period is significantly correlated with biomass and final yield [46,47]. Therefore, it may be possible to predict corn grain yield in-season for this study area, by comparing pre-silking period NDVIs to long-term normal growth curves.…”
Section: Stress-ndvi Residual Relationshipsupporting
confidence: 92%
“…Compared to Cluster B both cluster A and C have relatively larger absolute values (0.2-0.4) in NDVI residuals, indicating larger growth The correlation analysis summarized in Table 5 indicates that the NDVI residual derived from Landsat images reflects crop stress in the pre-silking period that in turn impacts final yield. This result is consistent with other studies that have found that NDVI from the middle to late vegetative period is significantly correlated with biomass and final yield [46,47]. Therefore, it may be possible to predict corn grain yield in-season for this study area, by comparing pre-silking period NDVIs to long-term normal growth curves.…”
Section: Stress-ndvi Residual Relationshipsupporting
confidence: 92%
“…Other studies (Martin et al 2007;Teal et al 2007;Raun et al, 2005) have shown that the coefficient of variation (CV) from NDVI measurements taken down the row varies widely throughout the growing season. Martin et al (2007) and Raun et al (2005) showed that CV's of NDVI measurements were highest in corn from growth stages V6-V8, and lowest from V10-VT.…”
Section: By-plant Sensingmentioning
confidence: 99%
“…By-plant variability in corn yields is well-documented (Martin et al, 2005;Teal, 2004;Freeman et al, 2007), expressing the need for management of N on a by-plant basis for corn. A study by Freeman et al (2007) revealed that NDVI, along with plant height measurements, can be used to predict by-plant corn forage yield.…”
Section: By-plant Sensingmentioning
confidence: 99%
See 2 more Smart Citations